Performance of Environmental and Energy Audit for Manufacturing Industrial Buildings. - Norfishah Ab Wahab; N. A. Sahril; A. Amiruddin; Zuhaila Mat Yasin; N. A. Salim; N. A. Rahmat; N. F. A. Aziz (Institute of Advanced Engineering and Science, 2018)
Environmental and energy audit of industrial building is important as it may help in providing a comfortable workplace for the staff as well as to observe the company’s environmental practices during operational hours while managing the energy usage in an efficient manner. It is also important in ensuring the company comply with applicable laws and regulations This paper discusses on the environmental and energy audit to identify the performance of environmental and energy efficiency in two manufacturing industrial buildings with heavy machineries. Analyses on the energy performance, visual comfort and thermal improvement including recommended solutions for optimization of energy efficiency and environmental aspects of the two buildings are presented. Energy efficiency and environmental aspects covered in this audit study are the illuminance of the building, indoor building temperature, relative humidity and carbon dioxide (CO2) percentage in indoor air quality. Jabatan Kerja Raya (JKR) standards is used as a benchmark to observe the illuminance of the buildings, Malaysian Standard 1525 (MS1525) is used as a quality control for temperature and relative humidity, while Department of Occupational Safety and Health, 2005 (DOSH 2005) is used as a quality control for CO2 percentage in air. Based on the results from the audit, the performance for both industrial building is compared. It was found that the energy efficiency and environmental performance for Factory A is better than Factory B.